Experimental research on development and validation of methods of quantitative determination of flavonoids and essential oil in solid multi-component capsules "Uroholum" - Shmalko, Oleksandr; Bevz, Nataliia; Vyshnevskyy, Igor; Vyshnevska, Liliia (ScienceRise: Pharmaceutical Science, 2019)
The aim. Development and validation of methods for the quantification of flavonoids and essential oils in solid multicomponent capsules for use in urology. Methods. To quantify the amount of flavonoids, a spectrophotometric technique was developed and validated using an Evolution 60 s spectrophotometer from Thermo Fisher Scientific, USA, to determine the essential oil - gravimetric method. Results. As a result of the study, a method was developed to quantify the sum of substances of the flavonoid structure of the total phytoextract in the form of capsules by spectrophotometric method and the sum of essential oils after pre-distillation with water vapour and extraction with organic solvent by gravimetry. Spectrophotometric quantification of flavonoid structure substances was performed after complexation reaction with aluminum salts (III) in acetic acid medium at an analytical wavelength of 410 nm. The calculation of the content of biologically active substances was performed by the standard method, which was used as a rutin. Validation parameters such as specificity, linearity, and precision have been studied for methods for quantifying the sum of substances of flavonoid structure and essential oils. Conclusions. Available and validated methods for the quantitative determination of the amount of biologically active substances of a dry multicomponent herbal extract in solid capsules have been developed and validated. The studied validation parameters meet the eligibility criteria